PENGARUH TAX PLANNING DAN GREEN INNOVATION TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI PEMEDIASI (Studi Empiris pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2019 – 2021) - Arini Nazivah; Kamaliah Kamaliah; Badriyah Nurul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
Company value is the company's performance which is reflected in the stock pricewhich reflects society's assessment of company performance (Cholifah & Kaharti,2021). This study aims to examine and analyze the effect of tax planning andgreen innovation on company value with profitability as a mediating variable inmanufacturing companies in the consumer goods industry sector listed on theIndonesia Stock Exchange in 2019-2021. The data used in this study is secondarydata obtained from the annual financial reports of companies in the consumergoods industry sector. The population in this study are all manufacturingcompanies in the consumer goods industry sector, totaling 59 companies listed onthe Indonesia Stock Exchange in 2019-2021. The sampling technique waspurposive sampling so 30 companies were included in the criteria. The dataanalysis technique used multiple linear regression analysis and path analysisusing SPSS (Statistical Product and Service Solutions) version 23. This studyfound that tax planning does not affect firm value. Green innovation andprofitability affect company value. Tax planning affects profitability by proxy forROA. Green innovation does not affect profitability. Tax planning has nosignificant effect on firm value which is mediated by profitability. Meanwhile,green innovation has a significant influence on company value which is mediatedby profitability. Keywords: Tax Planning, Green Innovation, Firm Value, Profitability